U.S. Law’s Artificial Cabining of Moral Rights: The Copyrightability Prerequisite and Cady Noland’s Log Cabin - Noh, Megan E. (The Columbia Journal of Law & the Arts, 2020)
In currently pending litigation, Cady Noland has sought to exercise the rights of attribution and integrity in relation to Log Cabin Façade; in this context, the Office’s denial of registration has resulted in complex legal arguments with both philosophical and practical implications. Against the backdrop of the Log Cabin controversy, this Article probes the conflict between the values and objectives underlying moral rights versus the “dominant,” economic theory of pre-existing copyright law. A critical question emerges: whether the “safeguards” imposed by limitations on the scope of copyrightability logically apply to the grant or denial of certain core moral rights protections for the single, original “copy” of an artwork. Concluding that they do not, this Article argues that recognition of an object as “artwork” by the relevant artistic community should “wag the dog” with respect to the artwork’s entitlement to such core moral rights protections, irrespective of its copyrightability.